On-line monitoring of microbial fuel cells operated with pulse-width modulated electrical load. (November 2015) - Coronado, J.; Tartakovsky, B.; Perrier, M.
Highlights: Real-time non-disruptive monitoring of MFC electrical parameters is demonstrated. MFC is operated with pulse-width modulated electrical load connection to enable real-time monitoring. Equivalent circuit model (ECM) analytical solutions are derived for high and low operating frequencies. On-line procedure for estimating internal resistance, internal capacitance, and open circuit voltage is proposed. ECM-based real-time parameter estimation offers insights on the MFC dynamics. Abstract: This study describes application of an equivalent circuit model (ECM) for on-line monitoring of microbial fuel cells (MFCs). ECM analytical solutions were derived for MFCs operated with pulse-width modulated electrical load connection at high and low frequencies. These analytical solutions were used to develop an on-line procedure for estimating MFC internal resistance, internal capacitance and open circuit voltage. The proposed parameter estimation and monitoring procedure was used to follow MFC startup performance as well as its performance at various organic loads. A comparison of ESM-based on-line estimations with conventional polarization tests confirmed feasibility of the proposed approach.